WACANA PESAN SINGKAT UCAPAN SELAMAT HARI RAYA (Discourse of Happy Eid Al-Fitr Greeting via Short Message) - Riani Riani (SAWERIGADING, 2015)
This study discusses the discourse of happy Eid Al-Fitr greeting via short message. The study is based on the development of communication technology, happy Eid Al-Fitr greeting nowadays can be transmitted via short messages (SMS) on mobile phone. This study aims to describe the discourse structure, language use (spelling, word choice, and sentence), language function, and speech acts in happy Eid Al-Fitr greeting. The study is a descriptive qualitative study because the data is lingual units (words and sentences) and data presentation is carried out descriptively. Data is collected by recording and documenting happy Eid Al-Fitr greeting short message in 2014 and 2015. The theory used in this study includes discourse, language use (spelling, word choice, and sentence), language function, and speech acts. The study showssome findings. First, the discourse structure of greeting consists of opening, content, and closing. Second, language use indicates that spelling on greeting emphasis on capital letter use and abbreviations; choice of words comprises of formal, informal, and local language style; sentence on greeting makes up singular and compound sentence accompanied by a deletion in the same element, in particular subject and clauses. Third, language function on greeting covers expressive, phatic, and poetic function. Forth, speech acts ingreeting imposes expressive and directive speech acts.